BUILDING A MADRASAH BRAND IMAGE TO BE HIGHLY COMPETITIVE THROUGH LOCAL WISDOM AND SOCIAL MEDIA - Sholeha, Mar’atus; Hidayati, Titiek Rohanah; Umam, Khotibul; Supriyadi, Agus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to describe the efforts of MTs. Nurul Huda Ranuyoso Lumajang in developing madrasas to be highly competitive, namely by branding the image of the Madrasah with Maqamad (Quran and Ma'had Madrasah) and Sasusi (One Child One Achievement). This research offers an alternative solution to develop madrasas that were previously uninterested and become popular. The research approach used is qualitative with a case study type. The results of this research are: First, the programs developed are the Habituation program, Tahfidz and Tahsin al-Quran (TTQ), Learning the Yellow Book, and One child, one achievement through class meeting activities. Planning the program begins with analyzing the strengths and weaknesses of the madrasah, formulating goals, creating programs, forming management, and utilizing social media. Second, the habituation program is carried out every day at 06.45-07.00. Especially on Fridays, the habitual activities are replaced with istighotsah activities and praying for the qubur expert. The TTQ program is held every Monday-Thursday at 07.00-08.00. Class meeting activities are held after semester exams. Third, the above programs are evaluated every month in conjunction with the madrasah's monthly evaluation meeting activities. The technical aspects include presenting the results and explaining the obstacles.